Solid Pseudopapillary Tumor of the Pancreas in a Child: Imaging Findings with Diffusion-Weighted MR Imaging - Rodrigues-Duarte, Hálio; Torrão, Helena; Coelho, Paulo; Noruegas, Maria; Sanches, Maria (JOP. Journal of the Pancreas, 2013)
Context Solid pseudopapillary tumor of the pancreas is a rare tumor more common in young girls and rare in males. Case report We present a case of a solid pseudopapillary tumor of the pancreas in a 13-year-old boy, with typical imaging features. Conclusions Our case report specifically illustrates the potential of diffusion-weighted imaging findings on solid pseudopapillary tumor in pediatric patients. Image: Doppler ultrasonography showing no apparent tumoral vascularization.